2016
DOI: 10.2337/dcs15-3003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Type 2 Diabetes: From “Guidelines” to “Position Statements” and Back

Abstract: Given the increased prevalence of type 2 diabetes worldwide, most patients are treated by their primary health care team (PHCT). PHCTs need guidance in choosing the best treatment regimen for patients, since the number of glucoselowering agents (GLAs) is rapidly increasing, as is the amount of clinical data regarding these drugs. The American Diabetes Association/European Association for the Study of Diabetes Position Statement emphasizes the importance of personalized treatment and lists drug efficacy, risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…For several decades, clinical practice guidelines for glycaemic control have focused on intensifying therapy to achieve target levels of risk factors, such as reducing HbA1c levels to less than 7.0% . However, it appears this overtreatment or treatment intensification is not harmless or associated with more benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several decades, clinical practice guidelines for glycaemic control have focused on intensifying therapy to achieve target levels of risk factors, such as reducing HbA1c levels to less than 7.0% . However, it appears this overtreatment or treatment intensification is not harmless or associated with more benefits.…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, clinical practice guidelines for glycaemic control have focused on intensifying therapy to achieve target levels of risk factors, such as reducing HbA1c levels to less than 7.0%. 44,45 However, it appears this overtreatment or treatment intensification is not harmless or associated with more benefits. A number of RCTs have shown that intensive glycaemic control directed at lower HbA1c targets is associated with only minor cardiovascular benefits, but increased adverse events such as mortality.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…However, type 2 diabetes is a complex disease for treatment, and there is no specific treatment algorithm that will be appropriate for all patients [17]. Recently, it has been reported that ketotifen as a mast cell stabilizer has a novel medication for obesity and diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Based on accumulating evidence, an expert group has endorsed the concept of short‐term intensive insulin (STII) therapy as an option for some patients with T2DM at the time of diagnosis . Notably, the latest Israeli guidelines suggest considering immediate, sometimes short‐term, insulin treatment for patients with HbA1c >9% or with symptoms …”
Section: List Of Pros and Cons Of Short‐term Intensive Insulin Theramentioning
confidence: 99%
“…5 Notably, the latest Israeli guidelines suggest considering immediate, sometimes short-term, insulin treatment for patients with HbA1c >9% or with symptoms. 6 It has been reported that nearly one-quarter (23%) of newly diagnosed T2DM patients in the US had an HbA1c ≥9.0% prior to initiation of treatment. 7 For such patients, initiating insulin is difficult, although it has been almost 10 years since the ACE/AACE Diabetes Road Map suggested insulin therapy for treatment-naïve patients with high HbA1c.…”
mentioning
confidence: 99%